Assessing the Internal Consistency of Process Rating Scale for Fault Diagnoses and Repairs in Diesel Engine Maintenance Practice in Technical and Vocational Institutions in Bayelsa State, Nigeria - Poripo, J. (Journal of Research in Industrial Technology and Educational Studies, 2026)
The study focused on the internal consistency of developed test for assessing technical vocational education and training students in motor vehicle mechanic work: diesel engine maintenance. The study adopted instrumentation design. It was carried out in Bayelsa State, Nigeria. The population of the study comprises of 64 motor vehicle mechanic work students. The instrument for data collection was the process skill rating scale test items consist of 45 (items) in service station mechanic work and diesel engine maintenance, they were found to be appropriate and internally consistent for inclusion. These items were developed using a task analysis questionnaire and were rated and validated by 3 experts in the study area. Cronbach alpha reliability coefficient was used to determine the internal consistency of the instrument. The internal consistency reliability coefficient is 0.87 and 0.88, with an overall index of 0.88 indicating a very high reliability, thus making them to be appropriate for inclusion for practical skills test. Mean scores were used to answer the research question, with ratings of 3.5 and above considered suitable for inclusion with Criterion value of (r ≥ 0.30). The findings revealed that all the developed service station mechanic work and diesel engine maintenance process skill rating scale instrument, possessed high reliability coefficients when considered using both the pairing and the grouping of the assessors using Kendall coefficient of concordance Tau (W). Thus, none of the items in each of the programme was dropped. Based on the findings, it was therefore recommended that the examination bodies in charge of conducting examinations for the vocational and technical colleges such as NBTE and NABTEB should integrate the process skill test items in their examination for certification of students in motor vehicle mechanic work at NTC level. It was also recommended that the developed process skill rating scale test items should be adopted by the National Examination Council (NECO) and West African Examination Council (WAEC) as a means of assessing motor vehicle mechanic work/ automobile technology for Nigerian institutions.
Keywords: Practical skills; Motor vehicle mechanic work; Technical and Vocational Education; Test